Biomechanical Loading Modulates Proinflammatory and Bone Resorptive Mediators in Bacterial-Stimulated PDL Cells. (25th May 2014) - Nogueira, Andressa Vilas Boas; Nokhbehsaim, Marjan; Eick, Sigrun; Bourauel, Christoph; Jäger, Andreas; Jepsen, Søren; Rossa, Carlos; Deschner, James; Cirelli, Joni Augusto
Abstract : The present study aimed to evaluate in vitro whether biomechanical loading modulates proinflammatory and bone remodeling mediators production by periodontal ligament (PDL) cells in the presence of bacterial challenge. Cells were seeded on BioFlex culture plates and exposed to Fusobacterium nucleatum ATCC 25586 and/or cyclic tensile strain (CTS) of low (CTSL) and high (CTSH) magnitudes for 1 and 3 days. Synthesis of cyclooxygenase-2 (COX2) and prostaglandin E2 (PGE2) was evaluated by ELISA. Gene expression and protein secretion of osteoprotegerin (OPG) and receptor activator of nuclear factor kappa-B ligand (RANKL) were evaluated by quantitative RT-PCR and ELISA, respectively. F. nucleatum increased the production of COX2 and PGE2, which was further increased by CTS. F. nucleatum -induced increase of PGE2 synthesis was significantly ( P < 0.05 ) increased when CTSH was applied at 1 and 3 days. In addition, CTSH inhibited the F. nucleatum -induced upregulation of OPG at 1 and 3 days, thereby increasing the RANKL/OPG ratio. OPG and RANKL mRNA results correlated with the protein results. In summary, our findings provide original evidence that CTS can enhance bacterial-induced syntheses of molecules associated with inflammation and bone resorption by PDL cells. Therefore, biomechanical, such as orthodontic or occlusal, loading may enhance the bacterial-induced inflammation and destruction in periodontitis.